The Moral Economy of Mobile Phones: Pacific Islands Perspectives - Robert J. Foster; Heather A. Horst (ANU Press, 2018)
The moral economy of mobile phones implies a field of shifting relations among consumers, companies and state actors, all of whom have their own ideas about what is good, fair and just. These ideas inform the ways in which, for example, consumers acquire and use mobile phones; companies promote and sell voice, SMS and data subscriptions; and state actors regulate both everyday use of mobile phones and market activity around mobile phones. Ambivalence and disagreement about who owes what to whom is thus an integral feature of the moral economy of mobile phones. This volume identifies and evaluates the stakes at play in the moral economy of mobile phones. The six main chapters consider ethnographic cases from Papua New Guinea, Fiji and Vanuatu. The volume also includes a brief introduction with background information on the recent `digital revolution' in these countries and two closing commentaries that reflect on the significance of the chapters for our understanding of global capitalism and the contemporary Pacific.
Keywords: 330